PEMBUATAN PORTOFOLIO DIGITAL REPRESENTATIF PADA MAHASISWA/I PROGRAM STUDI FOTOGRAFI POLITEKTIK NEGERI MEDIA KREATIF - syafriyandi syafriyandi; Irpan Riana; Nova Darmanto (Politeknik Negeri Media Kreatif, 2021)
ABSTRACTÂ Photography needs are now a part of daily activities, because the images that are produced can be used directly in expressing buying and selling activities and activities on new media. This phenomenon is a great opportunity for Creative Media State Polytechnic Photography Students. But the problem is that not many Photography students know the procedures for making a good or representative digital portfolio to be displayed in the online media for promotion of Photography Services. For this reason, this research has produced a representative digital portfolio for every photography student in order to increase the selling power to users of photography services both online and offline. This research uses a method with a qualitative approach. Data collection was also carried out by pretest and posttest control as a measuring tool for the success of the socialization of digital portfolio creation and literature study. The results of this study can be the basis for creating a digital portfolio as well as providing benchmarks for the marketing of Photography Services.Â Keywords: Photography, Digital Portofolio, new Media